Avaliação da qualidade de vida, ansiedade, estresse e depressão de cuidadores de pacientes com Síndrome de Down - Baldessim, Gabriela Baesteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The role of the caregiver of Down Syndrome (DS) is fundamental, since the degree of dependence of these individuals is variable, and can often overwhelm the life of the caregiver. Therefore, the objective of this study was to analyze the levels of anxiety, stress, depression and quality of life of caregivers of patients with DS attended at the CAOE (Center for the Assistance to Individuals with Disabilities) - UNESP (FOA), and to correlate to the degree of caregiver responsibility. Participants were 82 caregivers of patients with DS with a mean age of 58.19 years. The caregivers were initially submitted to an identification questionnaire. Then, to a quality-of-life assessment tool, the World Health Organization Quality of Life in its abbreviated form (WHOQOL- Bref), followed by the Inventory of Depression (Beck BDI-II) and anxiety (Beck BAI). The Stress Symptom Inventory (LIPP - ISSL) was then applied. The results were submitted to the chi-square test with significance level of p <0.05, for comparison between the groups. The study participants were divided into 2 groups, one of primary caregivers (G1) and other caregivers (G2). Most caregivers are primary (91.4%) and female (76.8%). The levels of depression and anxiety were not different for groups G1 and G2. As for stress symptoms, there was no statistical difference between the groups, both in the stress stages (p = 0.408) and in the physical symptoms (p = 0.668) and psychological symptoms (p = 0.745). In the quality of life, the physical domain (p = 0.673), psychological domain (p = 0.505), domain social relations (p = 0.235) and environment domain (p = 0.343) and total (p = 0.277), also did not have significant statistical difference. Caregivers of patients with DS did not present high levels of anxiety, stress and depression, nor did they have negative effects on quality of life, regardless of the degree of caregiver responsibility

O papel do cuidador de portadores de Síndrome de Down (SD) é fundamental, pois o grau de dependência destes indivíduos é variável, e muitas vezes pode sobrecarregar a vida do cuidador. Diante disto, o objetivo deste estudo foi analisar os níveis de ansiedade, estresse, depressão e a qualidade de vida de cuidadores de pacientes com SD, atendidos no CAOE (Centro de Assistência Odontológica à Pessoa com Deficiência) - UNESP (FOA), e correlacionar estes dados ao grau de reponsabilidade do cuidador. Participaram do estudo 82 cuidadores de pacientes com SD com faixa etária média de 58,19 anos. Os cuidadores foram inicialmente submetidos a um questionário de identificação. Em seguida, a um instrumento de avaliação de qualidade de vida, o World Health Organization Quality of Life em sua forma abreviada (WHOQOL- Bref), seguida pelo Inventário de Depressão (Beck BDI-II) e ansiedade (Beck BAI). Em seguida, foi aplicado o Inventário de Sintomas de Stress (LIPP - ISSL). Os resultados foram submetidos ao teste Qui-quadrado com nível de significância de p < 0,05, para comparação entre os grupos. Os participantes do estudo foram divididos em 2 grupos, sendo um de cuidadores primários (G1) e outros de demais cuidadores (G2). A maioria dos cuidadores são primários (91,4%) e do gênero feminino (76,8%). Os níveis de depressão e ansiedade não foi diferente para os grupos G1 e G2. Quanto aos sintomas de estresse, não houve diferença estatística entre os grupos, tanto nas fases do estresse (p= 0,408), quanto nos sintomas físicos (p=0,668) e sintomas psicológicos (p= 0,745). Na qualidade de vida, o domínio físico (p= 0,673), domínio psicológico (p= 0,505), domínio relações sociais (p= 0,235) e domínio ambiente (p= 0,343), auto avaliação da qualidade de vida (p= 0,296) e total (p= 0,277), também não tiveram diferença estatística significante. Os cuidadores de paciente com SD não apresentaram...
Keywords: Síndrome de Down; Depressão mental; Ansiedade; Estresse psicológico; Down Syndrome